PENGEMBANGAN FASILITAS PARKIR PANTAI BARON – PANTAI POK TUNGGAL BERBASIS PREFERENSI WISATAWAN - Cahyo, Hanif Nur; Hari Wibisono, Bambang (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2023)
Baron – Pok Tunggal Beach area is the most popular tourist destination in Gunungkidul, and the number of visitors who come to this beach also continues to increase yearly. This tourist area has been supported with parking facilities on every beach so that tourists can bring their vehicles to the beach area. However, the conditions of existing parking facilities can potentially cause air and noise pollution. Also, an accident between tourists and vehicles potentially happen. Access to this beach area is also quite difficult because of many steep uphill and downhill roads, sharp turns, and narrow roads with ravines and cliffs. According to that condition, traffic accidents potentially happen if the drivers and the vehicles are not in good condition. To resolve the problems is by developing the parking facilities into centralized parking facilities outside the beach area. The purpose of this study is to determine parking facility development according to the preferences of its user (tourists). 348 respondents represented the tourists' preferences by distributing a stated preference questionnaire. The analytical method used is crosstabs, helped by SPSS 16.0 app. The result of this study is that most respondents, or equivalent to 47% of respondents, chose the park-and-ride parking facility development.